Demand and growth regimes of the BRICs countries - Juan Manuel Campana; Jo\~ao Emboava Vaz; Eckhard Hein; Benjamin Jungmann (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2022)
We contribute to the recent debate in post-Keynesian economics (PKE), comparative political economy (CPE) and international political economy (IPE) on growth regimes. The paper presents an analysis of changes in demand-led growth regimes in the BRICs countries, Brazil, Russia, India, and China, after the Global Financial Crisis and the Great Recession 2007-09. It discusses and applies two approaches, a first one based on national income and financial accounting decomposition and a second one, based on the Sraffian Supermultiplier (SSM) growth model, distinguishing the dynamics of autonomous expenditure growth from those of the induced components of aggregate demand. It is argued that the SSM approach provides the bridge between the traditional approach based on national income and financial accounting decomposition and the analysis of growth drivers, both in PKE as well as in CPE and IPE. This is illustrated by pointing out some changes in the underlying political economy and economic policy growth drivers in each of the countries.
Keywords: E02; E11; E12; P16; P51; 330; Demand and growth regimes; growth decomposition; autonomous demand-led growth